2021
DOI: 10.1016/j.wroa.2021.100127
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemical advanced oxidation process for the treatment of urban stormwater

Abstract: Highlights Pre-production of concentrated H 2 O 2 before treatment reduced the system footprint. System design was optimized based on H 2 O 2 generation, storage, and activation. Optimization reduced cost and footprint of electrochemical stormwater treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…There are at least three possible mechanisms of anti-UVC activity of phenylpropanoids: (i) Scavenging of hydroxyl radical, (ii) supplementation of intracellular glutathione, and (iii) repair of cell damage caused by UVC irradiation, or hormetic growth stimulation. The following evidence supports in vivo 36: 2689-2699 (2022) the first mechanism: Tumor cells produce higher amounts of hydrogen peroxide than normal cells (25), and hydrogen peroxide is rapidly converted into hydroxyl radical by UV from an ultraviolet lamp (26). Mathew et al reported that phenylpropanoids scavenge hydroxyl radical more efficiently than superoxide radical, 1,1-diphenyl-2-picrylhydrazyl radical and 2,2'-azinobis-3-ethylbenzothiazoline-6-sulfonic acid radical, and gallic acid, a structural unit of tannin, showed slightly higher hydroxyl radical-scavenging activity than vanillin and vanillic acid (17).…”
Section: Discussionmentioning
confidence: 65%
“…There are at least three possible mechanisms of anti-UVC activity of phenylpropanoids: (i) Scavenging of hydroxyl radical, (ii) supplementation of intracellular glutathione, and (iii) repair of cell damage caused by UVC irradiation, or hormetic growth stimulation. The following evidence supports in vivo 36: 2689-2699 (2022) the first mechanism: Tumor cells produce higher amounts of hydrogen peroxide than normal cells (25), and hydrogen peroxide is rapidly converted into hydroxyl radical by UV from an ultraviolet lamp (26). Mathew et al reported that phenylpropanoids scavenge hydroxyl radical more efficiently than superoxide radical, 1,1-diphenyl-2-picrylhydrazyl radical and 2,2'-azinobis-3-ethylbenzothiazoline-6-sulfonic acid radical, and gallic acid, a structural unit of tannin, showed slightly higher hydroxyl radical-scavenging activity than vanillin and vanillic acid (17).…”
Section: Discussionmentioning
confidence: 65%
“…For comparison, a typical low-pressure UV lamp employed for UV/H 2 O 2 treatment consumes about 0.37 kWh/mol to produce photons (electrical to UV conversion efficiency = 35%). 69 Considering the inefficient absorption of UV light by H 2 O 2 in natural waters (i.e., more than 95% of the produced UV light is absorbed by other chromophores), 5 the energy consumption for generating • OH by the UV/H 2 O 2 process was estimated as 19 kWh/mol. Therefore, despite the loss of • OH on the stainless-steel surface (∼90%), the energy consumption for producing • OH that participated in the oxidation of aqueous species (i.e., 10 times the energy required to produce • OH) was estimated as 0.5 kWh/mol, which is over an order of magnitude lower than that of point-of-use UV/H 2 O 2 processes.…”
Section: ■ Environmental Implicationsmentioning
confidence: 99%
“…For small-scale systems, deposition of minerals on the surfaces of submerged lamps or loss of light emitted by suspended lamps through surface reflection further complicates the activation process. 5 As an alternative, the activation of H 2 O 2 by Fe(II) released from the oxidation of an iron anode has been used for industrial wastewater treatment. 6 Such electro-Fenton systems are impractical for drinking water and many other applications because they only produce high yields of • OH over a relatively narrow acidic pH range (i.e., pH 2−4) due to a shift in the reaction mechanism from one-electron processes that produce • OH to more selective oxidants (e.g., Fe[IV]) as the pH increases.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among these, electro-Fenton (EF), photo-electro-Fenton (PEF), photo-electro-ChemElectroChem catalysis (PEC), sono-electrolysis (SE), and sono-electro-Fenton (SEF) can be highlighted. [98][99][100] EAOPs have been already studied for the treatment of a variety of water matrices, including the degradation of pharmaceuticals, [101][102][103] landfill leachates, [104,105] urban stormwaters, [106,107] and carwash wastewater. [108] Even they have been applied at large scale, as the case of the automated disinfection of swimming pool water with boron doped diamond (BDD) anodes, where commercially available products such as Oxineo® and Sysneo® have been employed, [109] and the disinfection of ballast waters with EctoSys® cells.…”
Section: Ozonationmentioning
confidence: 99%